Immune Mechanisms Involved in Schistosoma mansoni-Cathepsin B Vaccine Induced Protection in Mice - Ricciardi, Alessandra; Zelt, Nicholas H.; Visitsunthorn, Kittipos; Dalton, John P.; Ndao, Momar (Frontiers in Immunology, 2018)
A vaccine against schistosomiasis would contribute to a long-lasting decrease in disease spectrum and transmission. Our previous protection studies in mice using Schistosoma mansoni Cathepsin B (Sm-Cathepsin B) resulted in 59% and 60% worm burden reduction with CpG oligodeoxynucleotides and Montanide ISA720 VG as adjuvants, respectively. While both formulations resulted in significant protection in a mouse model of schistosomiasis, the elicited immune responses differed. Therefore, in this study, we aimed to decipher the mechanisms involved in Sm-Cathepsin B vaccine-mediated protection. We performed in vitro killing assays using schistosomulae stage parasites as targets for lung-derived leukocytes and serum obtained from mice immunized with Sm-Cathepsin B adjuvanted with either Montanide ISA 720 VG or CpG and from non-vaccinated controls. Lung cells and immune sera from the Sm-Cathepsin B + Montanide group induced the highest killing (63%) suggesting the importance of antibodies in cell-mediated parasite killing. By contrast, incubation with lung cells from Sm-Cathepsin B + CpG immunized animals induced significant parasite killing (53%) independent of the addition of immune serum. Significant parasite killing was also observed in the animals immunized with Sm-Cathepsin B alone (41%). For the Sm-Cathepsin B + Montanide group, the high level killing effect was lost after the depletion of CD4+ T cells or Natural Killer (NK) cells from the lung cell preparation. For the Sm-Cathepsin B + CpG group, high parasite killing was lost after CD8+ T cell depletion, and a reduction to 39% was observed upon depletion of NK cells. Finally, the parasite killing in the Sm-Cathepsin B alone group was lost after the depletion of CD4+ T cells. Our results demonstrate how the different Sm-Cathepsin B formulations influence the immune mechanisms involved in parasite killing and protection against schistosomiasis.